PENAMBAHAN EKSTRAK SALAK SIDEMPUAN (Salacca sumatrana) UNTUK MENINGKATKAN PENERIMAAN EMULSI MINYAK OLEIN SAWIT MERAH - Sondang L Nadapdap; Budiyanto Budiyanto; Lukman Hidayat (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Carotenoids in red palm olein oil (RPOOO) have been scientifically proven to have good functional properties for the human health so that RPOOO has the potential to be used as one of the healthy drinks. One of the problems faced in the use of RPOO as a health drink is the taste and aroma is less interesting. This study aims to obtain the ratio of RPOO and salak sidempuan extract used to obtain stable emulsion, acceptable viscosity, and acceptable emulsion product. Four emulsions were prepared using 1% carbonmethylcellulosa as emulcifier and four different composition ratios of RPOO and salak extract were prepared. Emulsions characteristics and their sensory acceptability were investigated. The results of this study showed that the ratio of RPOO ratio and 1: 2 salak extract obtained the best stability with viscosity of 175 cP emulsion. In addition, emulsions with an RPOO ratio and 1:25 salak extract yield preferable levels of sensory attributes such as color, aroma and taste.